Innovative design of dun huang caisson lotus pattern in Sui Dynasty / Kang Sujuan ... [et al.] - Kang, Sujuan; Abdul Aziz, Mohd Nasiruddin; Ibrahim, Nur Hisham; Wang, Yingli (Universiti Teknologi MARA, Kedah, 2024)
This paper proposes a method for designing culture-creative products of the caisson Lotus pattern to better inherit the art of Dunhuang and meet contemporary aesthetic requirements. Initially, researcher analyzes the caisson Lotus patterns of Dunhuang in the Sui Dynasty. Then, a practical case study of the Lotus pattern is designed based on four stages of design practice, namely: association, concretization, transformation, and implementation. Literature reviews and case studies are the main research methods used in this paper. The literature review was used to summarize Lotus pattern types and characteristics. In the case study a series of workshops was conducted to implement cultural and creative product design. Research diaries, text analysis, observations, interviews and other data collection methods are used in the data collection process. This study shows that the Lotus pattern from the Sui dynasty is the most representative pattern. The design products created using the Lotus element are cultural, functional, and aesthetic and meet people's needs. It provides a feasible solution to the innovative pattern design problem.